Book Reviews. Issue 3 (1st September 2018) - Thomas, Sarah; Everly, Kathryn; Labanyi, Jo; Barker, Jesse; Blizzard, Mónica García; Poppe, Nicolas; Haaf, Rachel ten; Llamas-Rodriguez, Juan
The Child in Spanish Cinema, Sarah Wright (2013) Manchester and New York: Manchester University Press, 200 pp., ISBN 9-780-71909-052-3, h/bk, £70; 240 pp., ISBN 9-781-78499-379-5, p/bk, £16.99; ISBN 9-781-52610-320-8, eBook, £78.00El niño en el cine argentino de la postdictadura (1983–2008): alegoría y nostalgia, Sophie Dufays (2014) Woodbridge, Suffolk: Tamesis, 386 pp., ISBN 9-781-85566-285-8, h/bk, 99Children on the Threshold in Contemporary Latin American Cinema: Nature, Gender, and Agency, Rachel Randall (2017) Lanham, MD and London: Lexington Books, 284 pp., ISBN 978-1-49855-513-5, h/bk, 105 (£70); ISBN 978-1-49855-514-2, eBook, 99.50 (£65)Spanish Lessons: Cinema and Television in Contemporary Spain, Paul Julian Smith (2017) New York and Oxford: Berghahn, 168 pp., ISBN: 9-781-78533-108-4, h/bk, 95.00Ghostly Landscapes: Film, Photography, and the Aesthetics of Haunting in Contemporary Spanish Culture, Patricia M. Keller (2016) Toronto: University of Toronto Press, 280 pp., ISBN 9-781-44264-888-3, h/bk, 65.00Spanish Erotic Cinema, Santiago Fouz-Hernández (ed.) (2018) Edinburgh: Edinburgh University Press, 249 pp., ISBN 9-781-47440-047-3, h/bk, £75 ISBN 9-781-47444-096-7, p/bk, £24.99 ISBN 9-781-47440-048-0, eBook, £75Cosmopolitan Film Cultures in Latin America: 1896–1960, Rielle Navitski and Nicolas Poppe (eds) (2017) Bloomington, IN: Indiana University Press, 376 pp., ISBN 9-780-25302-646-0, p/bk, 38.00Pantallas Transnacionales: El Cine Argentino Y Mexicano Del Período Clásico, Ana Laura Lusnich, Alicia Aisemberg and Andrea Cuarterolo (eds) (2017) Buenos Aires: Imago Mundi, 480 pp., ISBN 9-789-50793-256-4, 420 ARSAfetos, Relações e Encontros Com Filmes Brasileiros Contemporâneos, Denilson Lopes (2017) São Paulo: Hucitec Editora, 200 pp., ISBN 9-788-58404-096-4, 52 BRSQueer Mexico: Cinema and Television since 2000, Paul Julian Smith (2017) Detroit, MI: Wayne State University Press, 176 pp., ISBN 9-780-81434-274-9, p/bk, 35.99